Foramen magnum as a tool for sexual dimorphism: A computed tomography study - Ashokkumar Kattimani; K Swetha; Harsha Bhayya; Shruti B Kardalkar (Wolters Kluwer Medknow Publications, 2023)
Background: Gender determination by skeletal relies predominantly on the skeletal radiology. Foramen magnum is in a favorable anatomic position, protected by soft tissue and skeleton of the head protecting the area for forensic examination. Foramen magnum being a relatively indestructible structure becomes an important tool in identification of gender. Objective: To study the vagueness and reliability of the foramen magnum (FM) in gender classification through the use of reconstructed computed tomography (CT) images. Materials and Method: A total of 200 patients (100 males and 100 females; age range, 18-60 years) were selected for the study. The FM measurements (sagittal, transverse, circumference, and area) were obtained from reformatted axial sections using a CT scan. Results: It was found that the mean FM sagittal diameter was 35.09 ± 2.48 mm, the FM transverse diameter was 28.76 ± 2.82 mm, the FM circumference was 110.56 ± 8.84 mm, and the FM area was 746.20 ± 108.47 mm2. According to Student's t-test results, in all measured parameters, there was a significant difference between the genders (P < 0.001). Conclusion: In all of the measured variables, there is a statistically significant difference present in the mean values of various parameters between both genders, with males having higher dimensions than female, indicative of sexual dimorphism.